Automatic speech recognition model development report - Mganga, Nelson; Jones-Garcia, Eliot; Koo, Jawoo (CGIAR System Organization, 2025)
This project builds on previous work where an earlier study sought to establish proof of concept on how speech recognition, along with natural language processing and text analysis techniques, can help to better identify farmer demands and target digital extension, particularly in the Global South.